Acute cholecystitis in eventration sac - Ruso Martínez, Luis; Yametti, Luis; Lombardi, Gerardo; Delgado, Bolívar (Cirugía del Uruguay, 1992)
The author presents a case of acute cholecystitis included in the eventration saccule in a transversal incision of the right hypochondrium in a obese patient. The interest of the communication lies in the analysis of the conditioners of this infrequent pathological association and the adopted surgical conduct.